Atividade anti-inflamatória e citotoxicidade dos extratos glicólicos de Cynara cardunculus var. scolymus (L.) Fiori (alcachofra), Myracrodruon urundeuva Allemão (aroeira-do-sertão) e Camellia sinensis (L.) Kuntze (chá verde) - Higa, Karen Cristiane [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The low cytotoxicity and anti-inflammatory action are interesting features for mouthwashes, toothpastes and dental medication. Therefore, it is necessary to evaluate these properties in plant glycolic extracts which can be ingredients of the formulation of these products. This study evaluated the following biological activities for each of the glycolic extracts of Cynara cardunculus var. scolymus (L.) Fiori (artichoke), Myracrodruon urundeuva Allemão (pepper tree) and Camellia sinensis (L.) Kuntze (green tea) in mouse macrophage cultures (RAW 264.7) by the exposure time of 5 min and 24 h. a) cytotoxicity by MTT method in 11 serial dilutions, the initial concentration of the extracts was 200 mg/mL. b) Anti-inflammatory activity after stimulation with lipopolysaccharide (LPS) of Escherichia coli was performed by immunoenzymatic test (ELISA) using specific antibodies to quantify IL-1 , TNF- and IL-10. The results were subordinated to statistical analyses (ANOVA and Turkey test), with p 0,05. The cytotoxicity of the extracts was dependent on dose and time. At 5 min exposure time, artichoke extract showed cytotoxicity at a concentration of 200 mg/mL. At 24 h exposure time, green tea showed cytotoxicity at the concentrations 50 mg/mL, pepper tree stimulated the proliferation of macrophages in the concentrations of 0,39mg/mL to 12.5 mg/mL and artichoke showed cytotoxicity at the concentrations 12.5 mg/mL. Green tea extract showed anti- inflammatory potential at a concentration of 12.5 mg/mL and was dependent on dose, promoting a decrease production of pro-inflammatory cytokines as IL-1 and TNF- . Pepper tree presented immunopotentiating action at a concentration of 12.5 mg/mL at 24 h of exposure time. Regarding artichoke, there is a need for further studies to identify their immunomodulatory action.

A baixa citotoxicidade e ação anti-inflamatória são características interessantes para enxaguatórios bucais, dentifrícios e medicamentos de uso odontológico. Sendo assim, é necessário avaliar estas propriedades nos extratos glicólicos vegetais que podem ser ingredientes das formulações desses produtos. O presente estudo avaliou as seguintes atividades biológicas para cada um dos extratos glicólicos de Cynara cardunculus var. scolymus (L.) Fiori (alcachofra), Myracrodruon urundeuva Allemão (aroeira-do-sertão) e Camellia sinensis (L.) Kuntze (chá verde) em culturas de macrófagos de camundongo (RAW 264.7) pelo tempo de exposição de 5 min e 24 h: a) atividade citotóxica pelo método do MTT em 11 diluições seriadas, sendo que a concentração inicial dos extratos foi de 200mg/mL. b) atividade anti-inflamatória, após estímulo com lipopolissacarídeo (LPS) de Escherichia coli pelo método ELISA quantificou IL-1β, TNF-α e IL-10. Os resultados foram analisados estatisticamente por ANOVA e teste de Tukey, com p ≤ 5%. A citotoxicidade dos extratos foi dose e tempo dependentes. No tempo de exposição de 5 min, o extrato de alcachofra apresentou citotoxicidade na concentração de 200 mg/mL. No tempo de exposição de 24 h, o chá verde apresentou citotoxicidade nas concentrações ≥ 50 mg/mL, aroeira-do-sertão estimulou a proliferação de macrófagos na concentração de 0,39 mg/mL a 12,5 mg/mL e a alcachofra apresentou citotoxicidade nas concentrações ≥ 12,5 mg/mL. O extrato de chá verde apresentou potencial anti-inflamatório na concentração de 12,5 mg/mL e foi dose dependente, promovendo diminuição da produção de citocinas pró-inflamatória, como IL-1β e TNF-α. A aroeira-do-sertão apresentou ação imunopotenciadora na concentração de 12,5 mg/mL no tempo de exposição de 24 h. Com relação a alcachofra há necessidade de novos estudos para identificar sua ação imunomoduladora.
Anti-inflammatory activity and cytotoxicity of glycolic extracts of Cynara cardunculus var. scolymus (L.) Fiori (artichoke), Myracrodruon urundeuva Allemão (pepper tree) and Camellia sinensis (L.) Kuntze (green tea)
Keywords: Anti-inflammatory activity of glycolic extract; Cytotoxicity; Artichoke; Pepper tree; Green tea; Ação anti-inflamatória de extratos glicólicos; Citotoxicidade; Alcachofra; Aroeira-do-sertão; Chá verde; RAW 264.7